Loudness Trumps Pitch in Politeness Judgments: Evidence from Korean Deferential Speech. (March 2020) - Idemaru, Kaori; Winter, Bodo; Brown, Lucien; Oh, Grace Eunhae
Social meaning is not conveyed through words alone, but also through how words are produced phonetically. This paper investigates the role of loudness and pitch in determining the perception of politeness-related judgments in Korean. It has been proposed that high pitch is universally associated with polite or deferential social meanings. In contrast to this, Experiment 1 examined the perceptual effect of pitch and found no effect. Experiment 2 tested the effect of loudness, and found that listeners associate quieter speech with deference. Finally, Experiment 3 investigated the simultaneous effects of loudness and pitch, and found again that loudness had a consistent effect, whereas pitch only had a weak effect. Analyses of individual differences suggest that in contrast to loudness, which is interpreted uniformly across Korean listeners, pitch has more variegated social meanings: Some listeners associate high pitch with deferential meaning, others associate low pitch with deferential meaning. Thus, we find loudness to be a more unambiguous indicator of deferential speech than pitch. These findings shed light on how different acoustic properties contribute to the indexing of social stances, and they suggest that the role of pitch in conveying politeness may have been overstated in past research.